ELECTRONIC WORD OF MOUTH MARKETING STRATEGY ANALYSIS ON SOCIAL MEDIA INSTAGRAM NANINE.ID - Nina Lestari; Cecep Safa'atul Barkah; Pratami Wulan Tresna; Arianis Chan (Universitas Mercu Buana, 2022)
The purpose of this research is to determine the dimension of electronic word-of-mouth (eWOM) consisting of intensity, the valence of opinion, and content applied in social media Instagram nanine.id. The population in this study is Instagram users who have visited nanine.id Instagram profile and heard about or used eWOM to get information about buying nanine.id products. Sampling technique to determine the sample to be used in this study using non-probability sampling technique, namely purposive sampling. Data collection techniques were carried out through in-depth interviews, questionnaires, and Forum Group Discussions (FGD). The data analysis method used is a descriptive statistical analysis technique. The result shows that the three dimensions of electronic word of mouth are already implemented with a very high category on Instagram nanine.id. The intensity dimension has an average score of 4.28, the valence of opinion has an average score of 4.25, and content has an average score of 4.56. To maintain and increase e-WOM through Instagram social media, there are several strategies proposed by the author, including consistently maintaining product and service quality, providing incentives, and creating interactive content.